Tinjauan Sosiologi Hukum Islam Terhadap Larangan Nikah Sasuku dalam Adat Minangkabau - Al Amin, Muhamad; Demiral, Ferik; Palevi, Reza; Mahyuzi, Indra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The prohibition of same-clan marriage in Minangkabau customs is still enforced by the Minangkabau community today, despite various differences in the application of leniencies and sanctions established in different nagari (villages) for those who engage in same-clan marriages. This prohibition was set by customary institutions at that time to address the social conditions of the community. Although the social conditions that led to this prohibition have changed, it remains upheld by the Minangkabau people to this day. In examining this phenomenon, this research utilizes an Islamic legal sociology approach to observe the shifts in social conditions that have occurred. This study aims to explore how the prohibition of same-clan marriage has maintained its existence within the Minangkabau community and continues to be practiced today. The research is primarily library-based, collecting various supporting literary sources. In Minangkabau customs, the prohibition of same-clan marriage is enforced to prevent various harms that may arise from such unions for their clans, making it considered taboo and bringing shame to their kin. This belief reinforces the community's perception of avoiding these marriages. The perception built within the Minangkabau community can be understood through the Islamic legal sociology approach as a means to prevent potential harms arising from this marriage (sad adz-dzari'ah). Additionally, the societal perception of the taboo surrounding this marriage can serve as a social control mechanism that strengthens the Minangkabau people's conviction to avoid such unions, allowing this custom to endure.